Knowledge integration in international SMEs – The effects on firm innovation and performance - Mohammad Javadinia Azari; Arild Aspelund; Ann Elida Eide (Cogent Business & Management, 2020)
This study aims to investigate the differential effects of internationalization and knowledge integration on the innovation capabilities and firm performance of international small- and medium-sized enterprises (SMEs). A K-means cluster analysis is performed on quantitative survey data from a sample of international SMEs in Norway followed by three-year-lagged data on the firms' financial growth. The study's findings show that it is the level of knowledge integration, rather than the degree of internationalization, which determines the range of sources for knowledge acquisition, and the innovation capabilities of international SMEs. However, both the degree of internationalization and knowledge integration are efficient differentiators for firm performance. SMEs that score high on both these two factors demonstrate significantly higher levels of firm performance in terms of innovation, internationalization, and growth.
Keywords: 650; internationalization; export; knowledge integration; small- and medium-sized enterprises; knowledge acquisition sources; innovation capabilities; firm performance; differential effects